Adolescents and morality : a study of some moral values and dilemmas of working adolescents in the context of a changing climate of opinion - Eppel, E. M. (Emanuel Montague) (Routledge, 2006)
The groundbreaking works in The Sociology of Youth and Adolescence set of the International Library of Sociology led the way to an authoritative understanding of how social interaction moulded young people. Careful observation of vulnerable and troubled children helped the leading sociologists, whose works are included in this set, to investigate how aggression, discipline, the struggle for recognition and the need to rebel shaped the personalities of the young. These are important texts for practitioners, students and teachers in health and social welfare.
"First published in 1966 by Routledge and Kegan Paul Ltd"--Title page verso.
Keywords: Youth -- England -- London.; London (England) -- Moral conditions.; Jeunesse -- Angleterre -- Londres.; FAMILY & RELATIONSHIPS -- Life Stages -- Adolescence.; FAMILY & RELATIONSHIPS -- Life Stages -- Teenagers.; Moral conditions; Youth; England -- London